The Night Market as a Space of Nostalgia Tourism: Study Case in Tanjung Uban: The Night Market as a Space of Nostalgia Tourism: Study Case in Tanjung Uban - Baitanu, Fitriana (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to examine the role of the Tanjung Uban Night Market as a space for nostalgia tourism. The research focuses on identifying how three main elements—local culinary heritage, market atmosphere, and social interaction—act as triggers of nostalgia, and how these experiences influence perceived value, satisfaction, place attachment, and revisit intentionn. Research methods: This study applied a qualitative descriptive approach. Data were collected through direct observation and in-depth interviews with 20 purposively selected participants, consisting of local visitors, vendors, and domestic tourists. Thematic analysis was employed to identify patterns and themes related to nostalgic experiences. Results and discussions: The findings revealed that culinary specialties such as otak-otak, gonggong, and traditional snacks, together with the lively yet simple atmosphere and strong social interactions, serve as powerful nostalgia triggers. These elements evoked emotional connections that enhanced visitor satisfaction, fostered cultural appreciation, and strengthened place attachment. The study underscores the role of night markets as socio-cultural spaces that reinforce destination identity and encourage revisit intention through nostalgic experiences Implication: The results emphasize the importance of integrating nostalgia-based experiences into local tourism development strategies. Policymakers and tourism stakeholders in Bintan should consider branding night markets not only as culinary destinations but also as cultural and emotional tourism spaces to enhance visitor engagement and loyalty